The clinical utility of electroencephalographic studies in children and adolescents at Tara Hospital - Mahuma, Othelia Omphemetse (My University, 2021)
Background: Electroencephalography (EEG) can be useful in the diagnosis of epilepsy and other neuropsychiatric disorders. There is a need to evaluate whether it is appropriately utilised, particularly among children and adolescents. Aim: To assess the clinical utility of EEG studies in children and adolescents at Tara Hospital. Objectives: To describe the reasons for referral for EEG studies, to determine the prevalence of abnormal EEGs and to examine their impact on the diagnosis and management of patients. Methods: A retrospective record review of all patients under age 18 referred for EEGs over a five-year period was conducted. Descriptive statistics were used to analyse the clinical profile and EEG findings, and inferential statistics to test associations between clinical variables and EEG findings. Results: 249 participants were enrolled; 63.4% were males,56.9% were between 5-12 years and 43% were between 13-18 years. 13.7% had an abnormal EEG, of which 70.6% were males. The proportion of abnormal EEGs was significantly higher in the 5-12 years age group compared to the 13-18 years age group (76.5% vs. 53.7%, p=0.013). The most common abnormal EEG finding was focal epileptiform activity (27%), followed by generalised epileptiform activity (24%) and focal slowing (18%). The rate of abnormal EEGs was found to be clinically significant in those with a history of seizures (p= 0.027), traumatic brain injury (p= 0.18) and comorbid medical conditions (p= 0.07). The overall demonstrable impact of the EEG in our study was 22%.Conclusion Our results confirm that EEG studies add value in the diagnosis and psychiatric management of children and adolescents
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Psychiatry, 2021